Microlending and Non-Accredited RE Investors as a Current Trend (Global Journal of Management and Business Research, 2019)
With billionaires like Donald Trump having made their fortunes from real estate, there is considerable interest from investors to put money in real estate for great returns (Thomas, 2016). For a long time, many were not motivated to invest in real estate, believing it to be an expensive venture, and therefore out of reach. To become an investor, one needed to fit within a certain criterion, thereby becoming known as an accredited investor. This means that investments were limited to only accredited investors. However, things have changed considerably, and now, it is possible for anyone to invest as a non-accredited investor. This is due to the growing popularity of crowdfunding. It was in May 2015 that the SEC updated their rules making it possible for more people to invest with ease. There are those who are familiar with crowd funding platforms, like GoFundMe, which they understand to be philanthropic in nature to help those that may be in need. However, some people have not yet realized that crowd funding can apply in the business world, particularly when it comes to real estate. How crowd funding works is that many people give small contributions on an online funding platform so that they can finance something (Freedman, 2015). Within the United States, crowdfunding appears to be slightly more popular than microlending.